Lanskap Linguistik Penamaan Kedai Kopi di Magelang - Kurniawati, Yenny (UPA Bahasa Universitas Tidar And HISKI Kedu, 2025)
This study aims to see the tendency of naming coffee shops in Magelang region connected with language loyalty. The researcher observed variations in language selection of words or phrases used for naming cafes. The researcher used qualitative description method to examine each word in the cafe naming. The results showed that English still dominates the naming of coffee shops. The results of the study in relation to Indonesian language loyalty show that the naming of coffee shops in Magelang does not show the country's language loyalty because the use of Indonesian is rarely found.